1982
DOI: 10.1002/1097-0142(19820401)49:7<1358::aid-cncr2820490709>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Failure of short-course multiple drug chemotherapy to benefit patients with recurrent or metastatic head and neck cancer

Abstract: Fifty-seven patients with advanced cancer (52 with squamous cell carcinoma of the head and neck) were treated with short-course, multiple drug chemotherapy using schedules that were similar to those proposed by Price et al. Chemotherapy consisted of vincristine, methotrexate and folinic acid rescue, bleomycin, and FU, with or without Adriamycin and hydroxyurea. Most patients had received radiation therapy. There were only six objective responses (one CR, five PR) and except for one patient who is alive without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…We emphasise that the advantages claimed for our protocol over cisplatincontaining combinations apply only to its use in previously unirradiated patients. Some authors have questioned our findings when they obtained inferior results in smaller numbers of previously treated patients or after altering the protocol [21,22]. We have already reported that schedule A chemotherapy appears no better than most other protocols in patients who have received prior radiotherapy, although it remains less toxic than some [4,9].…”
Section: Discussionmentioning
confidence: 74%
“…We emphasise that the advantages claimed for our protocol over cisplatincontaining combinations apply only to its use in previously unirradiated patients. Some authors have questioned our findings when they obtained inferior results in smaller numbers of previously treated patients or after altering the protocol [21,22]. We have already reported that schedule A chemotherapy appears no better than most other protocols in patients who have received prior radiotherapy, although it remains less toxic than some [4,9].…”
Section: Discussionmentioning
confidence: 74%
“…For the sake of completeness, we also checked the stability of compound 1 under acidic conditions and no changes were observed over time (data not shown). The microenvironment in tumors is generally acidic, [31] so it is expected that the investigated goldA C H T U N G T R E N N U N G (III)-dithiocarbamato derivatives would not undergo such an acid-base reaction at the tumor site.…”
Section: Resultsmentioning
confidence: 99%
“…We plan to extend this approach to probe over expression in other cancer cell lines and to investigate the use of the Schiff bases as tumor-targeted diagnostics. [40] Supporting Information Summary Experimental details; 1 H, 13 C and 119 Sn NMR spectra; highresolution mass spectra; X-ray structure for compound 4; crystallographic data for 4 and 5; and photophysical properties of compounds 1-6 in ethanol, DMF and DMSO.…”
Section: Discussionmentioning
confidence: 99%
“…The production of lactic acid under anaerobic conditions and the hydrolysis of ATP in an energy-deficient environment contribute to the acidic microenvironment which has been found in several tumor types. [13] In this context, pH differences have been the basis of cancer treatments and probes for diagnosis. [14] Fluorescent properties can be sensitive to pH and to other external factors such as viscosity and temperature.…”
Section: Introductionmentioning
confidence: 99%